2012
DOI: 10.1021/jp3057652
|View full text |Cite
|
Sign up to set email alerts
|

Inclusion Complexes between Amphiphilic Phenyleneethynylene Fluorophores and Cyclodextrins in Aqueous Media

Abstract: Binding events of cyclodextrins (CyD's) in aqueous media are important for designing and explaining the host-guest chemistry applied in sensing and controlled release systems. A water-soluble tricationic compound (3N(+)) with three branches of phenyleneethynylene fluorescent moieties and its related amphiphilic compounds (3C(-), N(0)N(+), N(+), and 2N(+)) are employed as molecular probes in the systematic characterization of the supramolecular interactions with CyD's (α, β, and γ). The strong fluorescence enha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The a, b, and g-CD have been used to increase water solubility of 2. 13 The ESI; Fig. S4 † showed that 2 can completely solute in HEPES buffer at pH 7.4.…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…The a, b, and g-CD have been used to increase water solubility of 2. 13 The ESI; Fig. S4 † showed that 2 can completely solute in HEPES buffer at pH 7.4.…”
Section: Resultsmentioning
confidence: 98%
“…The reaction set up was simple and the purication was easy. The structure of 2 was conrmed by 1 H-NMR, 13 C-NMR, and HRMS data (see ESI; Fig. S1-S3 †).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the presence of ␤-CD concentrations produced blue shift from 357 nm to 352 nm. The results indicated that PCA is entrapped more deeply into the ␤-CD cavity compared with ␣-CD and the formation of stable inclusion complexes (Lucas-Abellán et al, 2014;Rajendiran & Siva, 2014;Siripornnoppakhun et al, 2012;Stalin, Srinivasan, Sivakumar, & Radhakrishnan, 2014).…”
Section: Absorption and Fluorescence Spectral Analysismentioning
confidence: 99%